Pengaruh Program Pengalaman Lapangan Kependidikan (PLK) dan Efikasi Diri terhadap Minat Menjadi Guru - Rita Syofyan; Nur Sukma Hidayati; Rani Sofya (Universitas Negeri Padang, 2020)
This study was conducted to determine the effect of Field Experience Education Program or know as Praktik Lapangan Kependidikan (PLK) and self-efficacy on teacher interest in students of Economics Education, Faculty of Economics, Universitas Negeri Padang. This type of research is descriptive associative. The population in this study were students of economic education at the Faculty of Economics, Universitas Negeri Padang in 2015 who had or are currently taking the Educational Field Experience Program course with a population of 73 people. The data analysis technique used is path analysis. The results of this study indicate that (1) the Educational Field Experience Program (PLK) has a positive and significant effect on the self-efficacy of economic education students at the Faculty of Economics, Universitas Negeri Padang. (2) The Educational Field Experience Program (PLK) has a positive and significant effect on the interest in becoming a teacher for students of Economics Education, Faculty of Economics, Universitas Negeri Padang. (3) self-efficacy has a positive and significant effect on the interest in becoming a teacher in Economics Education students, Faculty of Economics, Universitas Negeri Padang.